Reasons for Delaying the Constriction Projects in Iraq - Areej A. Alsaadi; Redvan Ghasemlounia (International Journal of Engineering and Management Research, 2021)
This article dealt with construction projects in Iraq, and the research focused on the risks that may affect these projects. The purpose of this study is to determine the risks that construction projects are exposed to in Iraq and the methods of dealing in order to reduce these risks. Sometimes, if the construction projects are similar to each other in terms of configuration, requirements and purpose, then changing the project site is very sufficient to make these projects differ from each other and thus may be exposed to different risks. These are risks that negatively affect the implementation of these projects and may lead to delay or increase in their cost. Here a questionnaire is designed to collect data to identify risks that may occur during the construction project phases. This questionnaire was distributed electronically to several samples in the public and private sectors within state institutions in Iraq. After completion, the risks that these projects may be exposed to were identified. This was done with engineers and managers of companies and projects working in the public, private and joint sectors, and then these risks were analyzed by the Social Sciences for Packet Statistical Test program(SPSS).